Strain-specific galactose utilization by commensal E. coli mitigates Salmonella establishment in the gut. - Christopher Schubert; Jana Näf; Lisa Petukhov; Leanid Laganenka; Yassine Cherrak; Wolf-Dietrich Hardt (PLoS Pathogens)
Salmonella enterica serovar Typhimurium (S. Tm) is a major cause of gastrointestinal diseases worldwide. To date, options for prevention or curative therapy remain limited. The gut microbiota plays a protective role against enteric diseases, particularly in preventing establishment and proliferation of S. Tm. While most research has focused on microbiota-mediated pathogen exclusion during the later, inflammation-dominated stages of infection, little is known about how microbiota members mitigate S. Tm early gut colonization. To address this gap, we conducted 24 h in vivo competitive experiments using S. Tm and different commensal E. coli strains. We observed a significant reduction in pathogen load, which was strain-specific and particularly evident with E. coli 8178. To investigate the underlying molecular mechanisms, we performed an in vivo screen using a rationally designed S. Tm library-which includes a wide range of carbohydrate utilization mutants-both in the absence and presence of E. coli strains. Our findings revealed that E. coli 8178-mediated S. Tm competition was driven by the exploitation of galactose during the early stage of infection. Identifying galactose as a key metabolite in pathogen exclusion by gut microbiota members enhances our mechanistic understanding of microbiota-mediated protection and opens new avenues for developing microbiota- and dietary-based strategies to better control intestinal infections.